2020
DOI: 10.3390/nu12072041
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Intestinal Microbiota to Prevent Type 2 Diabetes and Enhance the Effect of Metformin on Glycaemia: A Randomised Controlled Pilot Study

Abstract: Early treatment may prevent or delay the onset of type 2 diabetes mellitus (T2DM) in individuals who are at high risk. Lifestyle interventions and the hypoglycemic drug metformin have been shown to reduce T2DM incidence. The effectiveness of such interventions may be enhanced by targeting environmental factors such as the intestinal microbiota, which has been proven to predict the response to lifestyle interventions and play a part in mediating the glucose-lowering effects of metformin. Shifts in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
100
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 57 publications
1
100
0
4
Order By: Relevance
“…Previous studies have reported that obesity and T2D are associated with a reduction of butyrate-producing bacteria and an increase in opportunistic pathogens ( 7 , 45 )⁠⁠. A recent randomized pilot study in which the impact of probiotic supplement on metformin’s effect on glycaemia in prediabetic subjects was assessed, has identified an increase in the relative abundance of Anaerotruncus colihominis (Cluster IV) only in participants receiving both metformin and the probiotic but not in participants taking either metformin or probiotic alone ( 46 )⁠⁠. Our results show that metformin alone can impact the relative abundance of different Anaerotruncus species in opposite directions; Anaerotruncus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that obesity and T2D are associated with a reduction of butyrate-producing bacteria and an increase in opportunistic pathogens ( 7 , 45 )⁠⁠. A recent randomized pilot study in which the impact of probiotic supplement on metformin’s effect on glycaemia in prediabetic subjects was assessed, has identified an increase in the relative abundance of Anaerotruncus colihominis (Cluster IV) only in participants receiving both metformin and the probiotic but not in participants taking either metformin or probiotic alone ( 46 )⁠⁠. Our results show that metformin alone can impact the relative abundance of different Anaerotruncus species in opposite directions; Anaerotruncus sp.…”
Section: Discussionmentioning
confidence: 99%
“…One potential mechanism by which the gut microbiome influences metabolic disease and T2D is via the fermentation of indigestible fibers into SCFAs (i.e., acetate, propionate, and butyrate) and others, and these metabolites can regulate blood glucose levels and insulin release [ 36 ]. Supplementation of other multi-strain probiotics, which include species of Bifidobacterium , Lactobacillus , and Streptococcus have demonstrated beneficial modulations in the gut microbiome, which are associated with increased secretion of SCFAs (mainly butyrate), improved glycemic control and insulin sensitivity, and reduced gut permeability in T2D [ 17 , 37 , 38 , 39 ]. Therefore, the inclusion of our newly-isolated human-origin Lactobacillus probiotics in our synbiotic yogurt may have prevented T2D progression by beneficially shifting the gut microbiome composition (i.e., increasing bifidobacteria and preventing the colonization of enteropathogens), leading to the production of beneficial metabolites and improved gut physiology.…”
Section: Discussionmentioning
confidence: 99%
“…This taxonomic group has been recently associated with improved insulin sensitivity in obese human subjects [ 28 ], alleviated obesity and metabolic dysfunctions in mice [ 29 ], and has been proven to negatively correlate with fasting blood glucose levels [ 30 ]. In addition, some recent studies of metformin effects have observed an increase in the abundance of this species or obtained associations with therapy outcomes [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%